A Security Paradox. The Influence Of Governance-Type Organized Crime Over the Surrounding Criminal Environment. (21st March 2020) - Aziani, Alberto; Favarin, Serena; Campedelli, Gian Maria
Abstract: This study empirically demonstrates how governance-type organized crime groups (OCGs) operate as an enforcer against volume crimes in the communities they control and argues that their ability to mitigate volume crimes forms an integral component of controlling their territory in the long term. This is because the costs incurred from deterring other crimes are offset by the tangible and intangible revenues that it facilitates. Indeed, combating volume crimes fosters an environment in which OCGs can conduct their activities unfettered by other criminals and law enforcement agencies, safeguard those businesses that pay them protection and curry favour amongst the population. Consequently, the present study verifies the validity of the security governance paradigm by conducting an econometric analysis of 11 different volume crimes.